Configuring and deploying open source with IBM WebSphere application server Liberty Profile - Credle, Rufus (IBM redbooks, 2015)
This IBM® Redbooks® publication explains the capabilities of IBM WebSphere® Application Server Liberty profile (Liberty profile), which is lightweight, easy to install, and fast to use. Liberty profile provides a convenient and capable platform for developing and testing your web and OSGi applications. The Liberty profile server is built by using OSGi technology and concepts. The fit-for-purpose nature of the run time relies on the dynamic behavior that is inherent in the OSGi framework and service registry. As bundles are installed or uninstalled from the framework, their services are automatically added or removed from the service registry. The result is a dynamic, composable run time that can be provisioned with only what your application requires and responds dynamically to configuration changes as your application evolves. This book can help you install, customize, and configure several popular open source technologies that can be deployed effectively with the Liberty profile server. The following popular open source toolkits for the Liberty profile server were selected for this book based on the significant enhancements they provide to the web application development process: Apache Maven Spring Framework Hibernate Jenkins Opscode Chef Arquillian MongoDB In this book, the Todo sample demonstrates the use of multiple open source frameworks or toolkits with the Liberty profile server, including Maven, MongoDB, Spring, JPA, Arquillian, Wicket, and others. The Todo sample is a simple application that can be used to create, update, and delete todo items and todo lists, and put the todo items into a related todo list.